Website E-Commerce Anyaman Bambu Kelurahan Kinilow Kota Tomohon Menggunakan Framework Laravel - Daniel Jackgie Ferson Lie; Chriestie Ellyanne Juliet Clara Montolalu; Mahardika Inra Takaendengan (Indonesian Journal of Intelligence Data Science, 2023)
Technology is developing very rapidly where all information is obtained quickly. One of the impacts of technological developments is in the sales business or in community-owned micro, small and medium enterprises, one of which is woven bamboo handicrafts in the Kinilow Village, Tomohon City. The purpose of this research is to design and build a sales website using the Laravel framework to make it easier for craftsmen to market their products. The method used in designing and building the system is the waterfall method. The resulting program is in the form of an e-commerce website for woven bamboo crafts that can assist craftsmen in selling and marketing products, as well as customers in buying and knowing woven products in stores.